Cyclooxygenase-2 and Cytosolic Phospholipase A2 Are Overexpressed in Mucinous Pancreatic Cysts. Issue 4 (April 2019) - Mensah, Elsie T.; Smyrk, Thomas; Zhang, Lizhi; Bick, Benjamin; Wood-Wentz, Christina M.; Buttar, Navtej; Chari, Suresh T.; Gleeson, Ferga C.; Kendrick, Michael; Levy, Michael; Pearson, Randall; Petersen, Bret T.; et al.
Abstract : OBJECTIVES: Expression of prostaglandin biosynthetic pathway enzymes in mucinous pancreatic cysts is unknown. Cyclooxygenase-2 (COX-2) inhibition is a potential cancer chemoprevention strategy for these lesions. We evaluated the expression of COX-2, cytosolic phospholipase A2 (cPLA2), and protein kinase B (AKT) in the epithelium of pancreatic cysts and correlated enzyme expression with aspirin (ASA) use and cyst fluid prostaglandin E2 (PGE2 ) concentration. METHODS: Pathology of 80 resected pancreatic cysts was reviewed. Expression of COX-2, cPLA2, and AKT was quantified by tissue immunohistochemistry immunoreactivity scores (IRSs). IRS values were compared between cyst types and (in 30 cases) with matched cyst fluid PGE2 concentrations. RESULTS: The mean IRS was higher in the epithelium of mucinous vs nonmucinous cysts for COX-2 (6.1 ± 4.7 vs 3.2 ± 2.8, P = 0.01) and cPLA2 (6.9 ± 3.0 vs 2.9 ± 2.9, P < 0.001). Cyst epithelial COX-2 expression was higher in mucinous cysts with low-grade dysplasia vs those with high-grade dysplasia or invasive carcinoma (IRS 8.0 ± 3.9 vs 1.5 ± 2.9, P < 0.001), whereas the opposite was found for cPLA2 (6.2 ± 3.0 vs 8.6 ± 2.3, P = 0.005). Cyst fluid PGE2 concentrations did not correlate with either the IRS or a history of low- to moderate-dose ASA use. CONCLUSIONS: COX-2 and cPLA2 are overexpressed in the epithelium of mucinous pancreatic cysts. COX-2 and/or cPLA2 inhibition might prevent the emergence or progression of mucinous pancreatic cysts, but higher doses of ASA or nonsteroidal anti-inflammatory drugs may be necessary to substantially inhibit cyst epithelial COX-2 activity.